Efficacy analysis of nano-insecticides from essential oils in controlling Sitophilus oryzae L. (Coleoptera: Curculionidae) in stored rice - Mohammad Hoesain; Anita Firnanda; Nanang Tri Haryadi; Sri Wahyuningsih; Fariz Kustiawan Alfarisy; Muh Adiwena; Ankardiansyah Pandu Pradana (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
This study evaluated nano-insecticides formulated from essential oils of mint (Mentha piperita), lemongrass (Cymbopogon citratus), basil (Ocimum basilicum), and eucalyptus (Eucalyptus sp.) for controlling Sitophilus oryzae, a major pest of stored rice. Essential oils were extracted using hydrodistillation, and nanoemulsions were prepared via a low-energy method. Efficacy tests conducted at concentrations of 1–5% showed that mint and lemongrass nano-insecticides were the most effective, achieving 100% mortality at 5% concentration within 168 hours and exhibiting superior repellency (mint oil reached 100% repellency at 5%). At 5% concentration, mint oil caused 25% mortality after 24 hours, increasing to 86% by 96 hours and reaching 100% by 120 hours, while lemongrass oil induced 10% mortality at 24 hours, 76% by 96 hours, and 100% by 144 hours. Their high efficacy is attributed to bioactive compounds such as menthol and citral, which disrupt the pest’s physiological processes. In contrast, eucalyptus and basil oils demonstrated comparatively lower mortality and repellency. These results highlight the potential of mint and lemongrass nano-insecticides as eco-friendly alternatives to synthetic pesticides and provide a sustainable option for integrated pest management in stored rice.